STRATEGIES OF INFORMATION DISCLOSURE - Steinfeld, Nili (AoIR Selected Papers of Internet Research, 2016)
How do users react when they are requested to provide personal information? The paper presents findings from two experiments conducted in distinct online environments, in which users were presented with a trade offer from an unfamiliar research body: Access to their personal Facebook profile in exchange for a monetary reward. The two experiments illustrate and characterize several strategies employed by participants in response to the trade offer.